White light colour fringe analysis for surface profiling - Ayisha Fathima Feroze Mohamed Arif (2019)
Single wavelength interferometry is a useful tool in the area of optical profilometry given its high sensitivity and resolution. However, its major drawbacks include its inability to quantify surface discontinuities and deformations that are greater than half a wavelength unambiguously. Nevertheless, multiple wavelength and white light interferometric techniques, with colour CCD cameras, have proven to be powerful alternatives that not only overcome the drawbacks of single wavelength interferometry but are also more effective in terms of being able to acquire multiple interference patterns simultaneously and producing high quality images. As such this report reviews the various multiple wavelength and white light interferometric techniques and discusses about how the phase shifting technique has been utilized as a phase evaluation procedure in order to ascertain the profile of the test surface without unambiguity. It should be noted that the various methods are reviewed on the basis that the test surface has a smooth profile Fundamental concepts such as those regarding interferometry, CCD cameras and cross talk have been gone through in this report for readers to gain good understanding of the review. At the end of this report readers will get to appreciate the developments in multi-colour interferometric techniques and their importance.